Analysis of the Implementation of 21st Century Manners Education in Overcoming Student Moral Decadence - Farisman Abdulah, Moh. Taufiq; Syahri, M.; Tinus, Agus (Pascasarjana Universitas KH. Abdul Chalim, 2025)
Moral decadence among madrasah students is increasingly alarming in the era of globalization and digitalization, as indicated by behaviors such as bullying, truancy, and a lack of courtesy. This phenomenon reflects the weak internalization of moral values despite the religious-based educational setting. MTs Nurwahid Gunung Sari has responded to this issue by implementing 21st-century manners education integrated into its curriculum. This study aims to evaluate the effectiveness of 21st-century manners education in shaping students’ character to become morally upright individuals. The main hypothesis states that integrating manners values can reduce deviant behaviors and strengthen students’ moral resilience amid globalization. This research employed a descriptive qualitative method involving ninth-grade students, teachers, the principal, and the vice principal of curriculum affairs. Data collection techniques included observations, in-depth interviews, and document studies, analyzed using the Miles and Huberman model. The findings indicate a significant improvement in students’ civility, exemplary behavior, and tolerance. Approximately 87% of students successfully applied manners values in daily life, although some still required further guidance. These results confirm that 21st-century manners education is effective as a preventive strategy against moral decadence. Further discussion highlights the need for content diversification and strengthening of the learning environment to optimize character formation and enable students to face global challenges with dignity.